Preparation method and application of lithium manganese iron phosphate positive electrode material

Through the first-stage sintering, cooling and second-stage sintering, the problem of manganese ion loss of lithium manganese iron phosphate positive electrode material is solved, its cycling performance and conductivity are improved, and better electrochemical performance and compaction density are achieved.

CN119118093AActive Publication Date: 2024-12-13GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411290970.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The lithium manganese iron phosphate positive electrode material has severe manganese ions lost during the circulation process, resulting in poor electrical and cyclic performance. The preparation process of the existing improved methods is complex and the performance improvement is not obvious.

Method used

The first-stage sintering, cooling and two-stage sintering are used to promote the in-situ diffusion of manganese and iron ions through high-temperature sintering. After cooling, the second-stage sintering is carried out at low temperature to eliminate structural defects and residual stresses to form iron-rich manganese phosphate on the surface of the particles. Iron lithium material.

Benefits of technology

Effectively reduce the dissolution of manganese ions, improve the circulation performance and conductivity of the positive electrode material, enhance compaction density, and improve electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118093A_ABST
    Figure CN119118093A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery materials, and particularly relates to a preparation method and application of a lithium iron manganese phosphate positive electrode material. The preparation method of the lithium manganese iron phosphate positive electrode material comprises the following steps: mixing a lithium manganese iron phosphate material, an iron source, a phosphorus source, a lithium source, a dopant and a carbon source, sanding, carrying out spray drying to obtain a precursor, and carrying out first-stage sintering, cooling and second-stage sintering on the precursor to obtain the lithium manganese iron phosphate positive electrode material. The precursor is subjected to two-stage sintering, the first-stage sintering promotes diffusion of manganese and iron ions at high temperature, and in-situ solid solution of manganese and iron is achieved; after cooling, second-stage sintering is carried out in an environment lower than the first-stage sintering temperature, so that structural defects generated in the material in a high-temperature solid solution process are eliminated; the outer layer of the prepared lithium manganese iron phosphate material is rich in iron, so that the dissolution of manganese ions is effectively reduced, the conductivity of the material is also improved, and the positive electrode material has relatively excellent electrochemical performance and long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a preparation method and application of a lithium manganese iron phosphate positive electrode material. Background Art

[0002] In recent years, the use of green, renewable, and carbon-free energy has become a general trend and an inevitable choice for the pursuit of sustainable development. Lithium-ion batteries are important electrochemical energy conversion and storage devices. Due to their advantages such as high energy density, good portability, and low self-discharge, they have become one of the most important ways to achieve new energy. At present, lithium iron phosphate materials are the most commonly used commercial lithium-ion battery cathode materials. This is attributed to their good platform stability, low cost, high safety, and good thermal stability. Therefore, they are widely used in electric vehicles and energy storage fields. However, compared with other cathode materials, the theoretical energy density of lithium iron phosphate (LiFePO4, LFP) is relatively low. In order to further improve the energy density of lithium-ion batteries, it is necessary to develop high-energy-density lithium iron phosphate cathode materials.

[0003] Lithium iron manganese phosphate (LiMn 1-x Fe x PO4, LMFP) can be regarded as a solid solution of lithium iron phosphate and lithium manganese phosphate (LiMnPO4, LMP). It has the same olivine structure as lithium iron phosphate and therefore has good safety. 2+ / Mn 3+ :~4.1V vs. Fe 2+ / Fe 3+ : ~3.4V), and the theoretical specific capacity is comparable to that of lithium iron phosphate. Therefore, lithium manganese iron phosphate cathode material has a higher energy density and has become an important candidate material to replace lithium iron phosphate. However, on the one hand, Mn 3+ There is a Jahn-Teller effect, which will cause structural distortion and degraded electrochemical performance during the cycle. On the other hand, Mn 3+ The obvious dissolution can easily cause manganese loss and structural distortion. Therefore, under high manganese conditions, the cycle performance of lithium manganese iron phosphate is poor. In order to improve the cycle properties of lithium manganese iron phosphate, the current mainstream methods include doping and coating (such as carbon coating, oxide coating and Li2MF6 coating, etc.), but most of these methods have complex preparation processes and no obvious performance improvement.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] In view of the problem of poor electrical properties and cycle performance of lithium iron manganese phosphate positive electrode materials in the prior art due to the loss of manganese ions, the purpose of the present invention is to provide a preparation method of lithium iron manganese phosphate positive electrode materials and applications thereof, aiming to reduce the dissolution of manganese during the circulation of lithium iron manganese phosphate materials and improve their electrochemical and cycle performance.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material, the preparation method comprising the following steps: The lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source are subjected to a second mixing and a second drying to obtain a precursor; the precursor is subjected to a first-stage sintering, a cooling, and a second-stage sintering to obtain a lithium manganese iron phosphate positive electrode material.

[0007] In an optional embodiment, the atmosphere of the first-stage sintering, cooling, and second-stage sintering process is nitrogen or argon, and the gas flow rate is 10-100 cm 3 / min, preferably 20 cm 3 / min.

[0008] In an optional embodiment, the sintering temperature of the first stage sintering is 700-850° C., and the sintering time is 6-12 hours.

[0009] In an optional embodiment, the temperature reduction refers to reducing the temperature to 200-350° C. after a stage of sintering is completed.

[0010] In an optional embodiment, the sintering temperature of the second stage sintering is 600-750° C., and the sintering time is 4-8 hours.

[0011] In an optional embodiment, the second mixing includes adding the lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source into water to prepare a second mixed solution, wherein the total mass fraction of the lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source in the second mixed solution is 20%-60%; the second mixed solution is subjected to a second sand milling to control the particle size D50 of the solid in the second mixed solution to be 0.35~0.60 µm.

[0012] In an optional embodiment, the second drying includes spray drying, and the air inlet temperature of the drying process is 180-240°C, and the air outlet temperature is 80-120°C.

[0013] In an alternative embodiment, the iron source is a soluble iron salt or iron hydroxide.

[0014] In an alternative embodiment, the dopant M includes at least one of compounds of magnesium, titanium, vanadium, niobium, chromium and cerium.

[0015] In an optional embodiment, the carbon source includes at least one of glucose, sucrose, polyvinyl alcohol, polyacrylamide, polyvinyl pyrrolidone, chitosan, melamine, fructose, cyclodextrin and polyethylene glycol.

[0016] In an optional embodiment, the molar ratio of the lithium element in the second lithium source, the iron element in the iron source, and the phosphorus element in the second phosphorus source is (1-1.05):1:(1-1.03).

[0017] In an optional embodiment, the molar ratio of the iron element in the iron source to the manganese element in the lithium manganese phosphate material is (1-5): (5-9).

[0018] In an optional embodiment, the molar ratio of the metal element in the dopant M to the iron element in the iron source is (0.005-0.05):1.

[0019] In an optional embodiment, the mass of the carbon source is 10%-20% of the theoretical output mass of carbon-free lithium iron manganese phosphate.

[0020] In an optional embodiment, the preparation method of the lithium manganese phosphate material includes: first mixing a manganese source, a first phosphorus source, a first lithium source and a dopant N, and freeze-drying to obtain a dry material; and sintering the dry material to obtain the lithium manganese phosphate material.

[0021] In an alternative embodiment, the manganese source includes at least one of manganese oxide, manganese hydroxide, a soluble manganese salt, manganese carbonate, and manganese phosphate.

[0022] In an optional embodiment, the first phosphorus source or the second phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphorus pentoxide.

[0023] In an optional embodiment, the first lithium source or the second lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, lithium oxalate, lithium acetate and lithium nitrate.

[0024] In an alternative embodiment, the dopant N includes at least one of compounds of magnesium, titanium, nickel, aluminum, vanadium, niobium, cobalt, chromium and cerium.

[0025] In an optional embodiment, the first mixing includes adding the manganese source, the first phosphorus source, the first lithium source and the dopant N into water to prepare a first mixed solution, wherein the total mass fraction of the manganese source, the first phosphorus source, the first lithium source and the dopant N in the first mixed solution is 20%-60%; performing a first sand milling on the first mixed solution to control the particle size D50 of the solid in the first mixed solution to be 0.2~0.4 µm.

[0026] In an optional embodiment, the molar ratio of the manganese element in the manganese source, the lithium element in the first lithium source, and the phosphorus element in the first phosphorus source is 1:(1-1.05):(1-1.03).

[0027] In an optional embodiment, the molar ratio of the metal element in the dopant N to the manganese element in the manganese source is (0.005-0.05):1.

[0028] In an optional embodiment, the sintering atmosphere includes at least one of nitrogen (N2), argon (Ar), 95% nitrogen / 5% hydrogen (95% N2 / 5% H2) and 95% argon / 5% hydrogen (95% Ar / 5% H2) (the percentage of gas here is volume percentage), and the gas flow rate is 10-100 cm 3 / min, preferably 20 cm 3 / min.

[0029] In an optional embodiment, the sintering temperature is 500-650° C., and the sintering time is 2-8 hours.

[0030] In a second aspect, the present invention further provides an application of a lithium iron phosphate positive electrode material prepared by the method for preparing a lithium iron manganese phosphate positive electrode material as described in the first aspect in a lithium ion battery.

[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The surface of the lithium iron manganese phosphate positive electrode material particles provided by the present invention is an iron-rich layer, which can effectively reduce the dissolution of manganese ions and improve the cycle performance of the positive electrode material. On the other hand, the iron-rich surface of the particles is beneficial to improving the conductivity of the positive electrode material, thereby reducing the coating amount of the carbon layer and increasing the compaction density of the lithium iron manganese phosphate material, thereby making the positive electrode material have better electrochemical performance and cycle performance.

[0032] (2) The present invention performs a first-stage sintering, cooling, and second-stage sintering treatment on the precursor. The first-stage sintering promotes the in-situ diffusion of manganese and iron ions at high temperature to achieve solid solution; after cooling, the second-stage sintering is performed at a lower temperature than the first-stage sintering temperature to eliminate the structural defects and residual stress generated inside the material during the high-temperature solid solution process, and finally obtains a lithium iron manganese phosphate positive electrode material with rich iron on the particle surface and uniform distribution of elements in the bulk phase. Moreover, the synthesis method for preparing the lithium iron manganese phosphate positive electrode material of the present invention is simple, the process is controllable, and it is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings are used to provide further understanding of the technical solution of this article and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of this article and do not constitute a limitation on the technical solution of this article.

[0034] Figure 1 It is a schematic diagram of the synthesis process of the lithium iron manganese phosphate positive electrode material in the present invention; Figure 2 The SEM images of the primary particles of lithium iron manganese phosphate positive electrode materials prepared in Example 1 (a), Example 5 (b) and Example 6 (c) of the present invention; Figure 3 This is the XRD diagram of the lithium manganese iron phosphate positive electrode material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present disclosure and should not be regarded as specific limitations of the present invention.

[0036] It should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturers are not specified, are all conventional products that can be purchased commercially.

[0037] The present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material, and the preparation method comprises the following steps: The lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source are subjected to a second mixing and a second drying to obtain a precursor; the precursor is subjected to a first-stage sintering, a cooling, and a second-stage sintering to obtain a lithium manganese iron phosphate positive electrode material.

[0038] The present invention performs one-stage sintering, cooling, and two-stage sintering on the precursor. The first-stage sintering at high temperature can promote the diffusion of manganese and iron ions to achieve in-situ solid solution of manganese and iron; the second-stage sintering after cooling is similar to tempering treatment, and the second-stage sintering is performed at a lower temperature (compared with the first-stage sintering temperature) after cooling. On the one hand, it can eliminate structural defects and residual stresses generated inside the material during the high-temperature solid solution process and improve the diffusion of lithium ions; on the other hand, it can further promote the diffusion of manganese and iron elements, thereby obtaining a lithium manganese iron phosphate positive electrode material with iron-rich particle surface and uniformly distributed elements in the bulk phase.

[0039] In some embodiments, the second mixing includes adding lithium manganese phosphate material, an iron source, a second phosphorus source, a second lithium source, a dopant M and a carbon source into water to prepare a second mixed solution.

[0040] In some embodiments, the second mixing includes adding lithium manganese phosphate material, an iron source, a second phosphorus source, a second lithium source, a dopant M and a carbon source into water to prepare a second mixed liquid, and then performing a second sand milling on the second mixed liquid to make the solid particle size in the second mixed liquid meet the standard.

[0041] In some embodiments, the second drying is carried out by spray drying, and the inlet air temperature of the spray drying is 180-240°C, for example, 180°C, 200°C, 220°C or 240°C, and the outlet air temperature is 80-120°C, for example, 80°C, 100°C, 120°C or 120°C, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0042] In some embodiments, the total mass fraction of the lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source in the second mixed solution is 20%-60%, for example, it can be 20%, 30%, 40% or 60%, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0043] In some embodiments, the particle size D50 of the solid in the second mixed liquid is 0.35-0.60 µm, for example, 0.35 µm, 0.40 µm, 0.45 µm, 0.50 µm or 0.60 µm, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0044] In the process of preparing the lithium iron manganese phosphate material of the present invention, the particle size of the solid in the second mixed solution will affect the electrochemical properties and compaction density of the prepared lithium iron manganese phosphate positive electrode material. If the solid particle size is too large or too small, the diffusion rate of lithium ions will decrease, thereby resulting in a low specific capacity of the lithium battery prepared from the positive electrode material.

[0045] In some embodiments, the molar ratio of the lithium element in the second lithium source, the iron element in the iron source and the phosphorus element in the second phosphorus source is (1-1.05):1:(1-1.03), for example, it can be 1:1:1, 1.02:1:1.01, 1.04:1:1.02 or 1.05:1:1.03, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0046] In some embodiments, the molar ratio of the iron element in the iron source to the manganese element in the lithium manganese phosphate material is (1-5): (5-9), for example, it can be 5:5, 4:6, 3:7, 2:8 or 1:9, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0047] In some embodiments, the molar ratio of the metal element in the dopant M to the iron element in the iron source is (0.005-0.05):1, for example, it can be 0.005:1, 0.015:1, 0.03:1, 0.04:1 or 0.05:1, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0048] In some embodiments, the mass of the carbon source is 10%-20% of the theoretical output mass of carbon-free lithium manganese iron phosphate, for example, it can be 10%, 15% or 20%, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0049] In some embodiments, the sintering temperature of the first stage sintering is 700~850℃, for example, it can be 700℃, 750℃, 800℃ or 850℃, and the sintering time is 6-12h, for example, it can be 6h, 8h, 10h or 12h, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0050] In some embodiments, the cooling refers to cooling to 200-350°C after a period of sintering, for example, it can be 200°C, 250°C, 300°C or 350°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0051] In some embodiments, the sintering temperature of the second stage sintering is 600-750°C, for example, it can be 600°C, 650°C, 700°C or 750°C, and the sintering time is 4-8h, for example, it can be 4h, 5h, 7h or 8h, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0052] In the process of preparing lithium manganese iron phosphate material of the present invention, in order to promote the diffusion of manganese to the surface of particles and the diffusion of iron to the inside of particles, and then realize the in-situ solid solution of manganese and iron, the temperature of the first sintering will be higher than the temperature of the second sintering. In addition, the level of the second sintering temperature will further affect the degree of iron-manganese solid solution. If the sintering temperature is too high, manganese will continue to diffuse outward, and the manganese content on the particle surface will be high; if the sintering temperature is too low, the atomic diffusion is poor, and the defect elimination is insufficient.

[0053] In some embodiments, the preparation method of the lithium manganese phosphate material includes: first mixing a manganese source, a first phosphorus source, a first lithium source and a dopant N, and freeze-drying to obtain a dry material; and sintering the dry material to obtain the lithium manganese phosphate material.

[0054] In some embodiments, the first mixing includes adding a manganese source, a first phosphorus source, a first lithium source, and a dopant N into water to prepare a first mixed solution.

[0055] In some embodiments, the first mixing includes adding a manganese source, a first phosphorus source, a first lithium source, and a dopant N into water to prepare a first mixed solution, and then performing a first sand milling on the first mixed solution to ensure that the solid particle size in the first mixed solution meets the standard.

[0056] In some embodiments, the freeze drying refers to first freezing the mixed material after the first sand grinding with liquid nitrogen and then placing it in a vacuum environment for sublimation drying.

[0057] In the method for preparing lithium manganese phosphate material of the present invention, a freeze-drying step is adopted to prevent the primary particles of lithium manganese phosphate from agglomerating too seriously.

[0058] In some embodiments, the total mass fraction of the manganese source, the first phosphorus source, the first lithium source and the dopant N in the first mixed solution is 20%-60%, for example, it can be 20%, 40% or 60%, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0059] In some embodiments, the particle size D50 of the solid in the first mixed liquid is 0.2-0.4 µm, for example, 0.2 µm, 0.25 µm, 0.3 µm, 0.35 µm or 0.4 µm, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0060] In some embodiments, the molar ratio of the manganese element in the manganese source, the lithium element in the first lithium source and the phosphorus element in the first phosphorus source is 1:(1-1.05):(1-1.03), for example, it can be 1:1:1, 1:1.03:1.02, 1:1.04:1.02 or 1:1.05:1.03, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0061] In some embodiments, the molar ratio of the metal element in the dopant N to the manganese element in the manganese source is (0.005-0.05):1, for example, it can be 0.005:1, 0.015:1, 0.03:1, 0.04:1 or 0.05:1, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0062] In some embodiments, the sintering temperature is 500-650°C, for example, 500°C, 550°C, 600°C or 650°C, and the sintering time is 2-8h, for example, 2h, 4h, 6h or 8h, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0063] The lithium iron manganese phosphate positive electrode material of the embodiment of the present invention is shown in the accompanying drawings Figure 1 The synthetic scheme shown was used for preparation.

[0064] Example 1 This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, the method comprising the following steps: S1. Lithium carbonate, manganese tetraoxide, phosphoric acid and nickel oxide were weighed and added to deionized water in a molar ratio of lithium: manganese: phosphorus: nickel of 1.04:1:1.02:0.015 to prepare a mixed solution with a total mass fraction of 60%; the mixed solution was sand-milled until the particle size D50 of the solid in the mixed solution was 0.25 µm, and then frozen with liquid nitrogen, and then sublimated and dried (freeze-dried) in a vacuum oven to obtain a dried material; the freeze-dried powder was then sintered in an atmosphere of 95% N2 / 5% H2 at an air flow rate of 20 cm 3 / min, the sintering temperature is 620℃, and the holding time is 8h to obtain lithium manganese phosphate material.

[0065] S2. First, disperse the lithium manganese phosphate powder in deionized water, weigh lithium acetate, ferrous sulfate, phosphoric acid and niobium dioxide (wherein the molar ratio of manganese: iron is 7:3) according to the molar ratio of lithium: iron: phosphorus: niobium of 1.04:1:1.02:0.015, and add them to the above dispersion, and then weigh glucose and fructose (the mass ratio of the two is 1:1, and the total mass is 15% of the theoretical output mass of carbon-free lithium manganese iron phosphate) and add them to the above dispersion to prepare a mixed solution with a total mass fraction of 40%; sand grind the mixed solution until the particle size D50 of the solid in the mixed solution is 0.40 When the particle size was less than 100 μm, spray drying was performed, and the inlet air temperature was 200°C and the outlet air temperature was 90°C to obtain a dried precursor; the dried precursor was sintered in a N2 atmosphere, and the temperature of the first sintering stage was 800°C, and the holding time was 8 hours. Then the temperature was lowered to 200°C, and then the temperature was raised to the second sintering stage, and the sintering temperature was 680°C, and the holding time was 4 hours. The airflow rate during the sintering process was 20 cm 3 / min. After the material is discharged, it is crushed and then passed through a 300-mesh sieve to obtain lithium manganese iron phosphate positive electrode material (LM 0.7 F 0.3 P).

[0066] Example 2 This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, the method comprising the following steps: S1. Lithium carbonate, manganese tetraoxide, phosphoric acid and nickel oxide were weighed and added to deionized water in a molar ratio of lithium: manganese: phosphorus: nickel of 1:1:1:0.005 to prepare a mixed solution with a total mass fraction of 20%; the mixed solution was sand-milled until the particle size D50 of the solid in the mixed solution was 0.20 µm, and then frozen with liquid nitrogen, and then sublimated and dried (freeze-dried) in a vacuum oven to obtain a dried material; the freeze-dried powder was then sintered in an atmosphere of 95% N2 / 5% H2 at an air flow rate of 20 cm 3 / min, the sintering temperature is 500℃, and the holding time is 6h to obtain lithium manganese phosphate material.

[0067] S2. First, disperse the lithium manganese phosphate powder in deionized water, weigh lithium acetate, ferrous sulfate, phosphoric acid and niobium dioxide (wherein the molar ratio of manganese: iron is 5:5) according to the molar ratio of lithium: iron: phosphorus: niobium of 1:1:1:0.005, and add them to the above dispersion, and then weigh glucose and fructose (the mass ratio of the two is 1:1, and the total mass is 10% of the theoretical output mass of carbon-free lithium manganese iron phosphate) and add them to the above dispersion to prepare a mixed solution with a total mass fraction of 40%; sand grind the mixed solution until the particle size D50 of the solid in the mixed solution is 0.35 When the particle size is 100 μm, spray drying is performed, the air inlet temperature is 240°C, and the air outlet temperature is 80°C to obtain a dried precursor; the dried precursor is sintered in a N2 atmosphere, the temperature of the first sintering stage is 700°C, the holding time is 12 hours, then the temperature is lowered to 350°C, and then the temperature is raised to the second sintering stage, the sintering temperature is 600°C, and the holding time is 8 hours. The air flow rate during the sintering process is 20 cm 3 / min. After the material is discharged, it is crushed and then passed through a 300-mesh sieve to obtain lithium manganese iron phosphate positive electrode material (LM 0.5 F 0.5 P).

[0068] Example 3 This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, the method comprising the following steps: S1. Lithium carbonate, manganese tetraoxide, phosphoric acid and nickel oxide are weighed and added into deionized water in a molar ratio of lithium: manganese: phosphorus: nickel of 1.05:1:1.03:0.05 to prepare a mixed solution with a total mass fraction of 50%; the mixed solution is sand-milled, and when the particle size D50 of the solid in the mixed solution is 0.40 µm, it is frozen with liquid nitrogen, and then sublimated and dried (freeze-dried) in a vacuum oven to obtain a dried material; the freeze-dried powder is then sintered in an atmosphere of 95% N2 / 5% H2, with an air flow rate of 20 cm3 / min, a sintering temperature of 650°C, and a holding time of 2h to obtain a lithium manganese phosphate material.

[0069] S2. First, disperse the lithium manganese phosphate powder in deionized water, weigh lithium acetate, ferrous sulfate, phosphoric acid and niobium dioxide (wherein the molar ratio of manganese: iron is 9:1) according to the molar ratio of lithium: iron: phosphorus: niobium of 1.05:1:1.03:0.05, and add them to the above dispersion, and then continue to weigh glucose and fructose (the mass ratio of the two is 1:1, and the total mass is 20% of the theoretical output mass of carbon-free lithium manganese iron phosphate) and add them to the above dispersion to prepare a mixed solution with a total mass fraction of 50%; sand grind the mixed solution until the particle size D50 of the solid in the mixed solution is 0.60 When the particle size was 0.1 μm, spray drying was performed, and the inlet air temperature was 180°C and the outlet air temperature was 120°C to obtain a dried precursor; the dried precursor was sintered in a N2 atmosphere, and the temperature of the first sintering stage was 850°C, and the holding time was 6 hours. Then the temperature was lowered to 250°C, and then the temperature was raised to the second sintering stage, and the sintering temperature was 750°C, and the holding time was 6 hours. The airflow rate during the sintering process was 20 cm 3 / min. After the material is discharged, it is crushed and then passed through a 300-mesh sieve to obtain lithium manganese iron phosphate positive electrode material (LM 0.9 F 0.1 P).

[0070] Example 4 S1. Lithium carbonate, manganese tetraoxide, phosphoric acid and nickel oxide were weighed and added to deionized water in a molar ratio of lithium: manganese: phosphorus: nickel of 1.05:1:1.02:0.01 to prepare a mixed solution with a total mass percentage of 40%; the mixed solution was sand-milled until the particle size D50 of the solid in the mixed solution was 0.25 µm, and then frozen with liquid nitrogen, and then sublimated and dried (freeze-dried) in a vacuum oven to obtain a dried material; the freeze-dried powder was then sintered in an atmosphere of 95% N2 / 5% H2 at an air flow rate of 20 cm 3 / min, the sintering temperature is 600℃, and the holding time is 8h to obtain lithium manganese phosphate material.

[0071] S2. First, disperse the lithium manganese phosphate powder in deionized water, weigh lithium acetate, ferrous sulfate, phosphoric acid and niobium dioxide (wherein the molar ratio of manganese: iron is 6:4) according to the molar ratio of lithium: iron: phosphorus: niobium of 1.05:1:1.02:0.01, and add them to the above dispersion. Then, weigh glucose and polyethylene glycol (the mass ratio of the two is 1:1, and the total mass is 15% of the theoretical output mass of carbon-free lithium manganese iron phosphate) and add them to the above dispersion to prepare a mixed solution with a total mass fraction of 30%. Sand grind the mixed solution until the particle size D50 of the solid in the mixed solution is 0.40 When the particle size was less than 100 μm, spray drying was performed, and the inlet air temperature was 200°C and the outlet air temperature was 90°C to obtain a dried precursor; the dried precursor was sintered in a N2 atmosphere, and the temperature of the first sintering stage was 800°C, and the holding time was 8 hours. Then the temperature was lowered to 200°C, and then the temperature was raised to the second sintering stage, and the sintering temperature was 680°C, and the holding time was 4 hours. The airflow rate during the sintering process was 20 cm 3 / min. After the material is discharged, it is crushed and then passed through a 300-mesh sieve to obtain lithium manganese iron phosphate positive electrode material (LM 0.6 F 0.4 P).

[0072] Example 5 S1. Compared with Example 1, the molar ratio of lithium: manganese: phosphorus: nickel is changed to 1.05:1:1.02:0.015, and the other steps remain unchanged.

[0073] S2. Compared with Example 1, the molar ratio of lithium: iron: phosphorus: niobium is changed to 1.05:1:1.02:0.01, the carbon source is changed to glucose and polyethylene glycol, the cooling temperature is changed to 250°C, the temperature of the second sintering stage is changed to 700°C, and the other steps remain unchanged.

[0074] Example 6 S1. Compared with Example 4, the total mass fraction of the mixed solution is changed to 30%, the sand grinding is changed to a particle size D50 of 0.3 µm, and the other steps remain unchanged.

[0075] S2. Compared with Example 4, the sand grinding was changed to a particle size D50 of 0.45 µm, and the molar ratio of manganese: iron was changed to 7:3; the carbon source was changed to glucose and polyvinyl alcohol, and the total mass of the two was 12% of the theoretical output mass of lithium manganese iron phosphate; the inlet temperature of the spray drying was changed to 180°C, and the outlet temperature was changed to 80°C, and the other steps did not change.

[0076] Example 7 S1. Compared with Example 4, the sintering temperature is changed to 650° C., and the other steps remain unchanged.

[0077] S2. Compared with Example 4, the carbon source is changed to glucose and cyclodextrin, the temperature of the second sintering stage is changed to 720° C., and the other steps remain unchanged.

[0078] Example 8 S1. Compared with Example 4, the particle size D50 of the solid in the mixed solution was changed to 0.30 μm by sand grinding, and the molar ratio of manganese: iron was changed to 8:2. The other steps remained unchanged.

[0079] S2. The steps are the same as those in Example 4.

[0080] Example 9 Compared with Example 1, the step S2 is changed to sand-grind the solid in the mixed solution to a particle size D50 of 0.30 μm, and the other steps are unchanged.

[0081] Example 10 Compared with Example 1, the step S2 is changed to sand-grind the solid in the mixed solution to a particle size D50 of 0.50 μm, and the other steps are unchanged.

[0082] Embodiment 11 Compared with Example 1, the molar ratio of manganese:iron in step S2 is changed to 5:5, and the other steps are not changed.

[0083] Example 12 Compared with Example 1, the molar ratio of manganese to iron in step S2 is changed to 9:1, and the other steps remain unchanged.

[0084] Embodiment 13 Compared with Example 1, the temperature of the second sintering stage in step S2 is changed to 600° C., and the other steps remain unchanged.

[0085] Embodiment 14 Compared with Example 1, the temperature of the second sintering stage in step S2 is changed to 750° C., and the other steps remain unchanged.

[0086] Comparative Example 1 Compared with Example 4, the iron source is added during step S1 to prepare lithium manganese iron phosphate positive electrode material.

[0087] S1. Change the molar ratio of lithium: iron: manganese: phosphorus: nickel: niobium to 1.05:1:1:1.02:0.01:0.01, and the other steps remain unchanged.

[0088] S2. The lithium manganese iron phosphate material obtained in step S1 is mixed with a carbon source (glucose and polyethylene glycol), and a two-stage sintering process is directly performed. The sintering process is the same as step S2 of Example 4.

[0089] Comparative Example 2 Compared with Example 5, the second sintering process is not performed during step S2, and the remaining steps remain unchanged.

[0090] Comparative Example 3 Compared with Example 5, the soluble ferrous sulfate is replaced with insoluble ferric phosphate during step S2, and the remaining steps remain unchanged.

[0091] The lithium iron manganese phosphate positive electrode materials prepared in Examples 1 to 14 and Comparative Examples 1 to 3 were tested for specific surface area and compaction density, and button cells were prepared to evaluate electrochemical performance, specifically including the following steps: (1) Specific surface area test The specific surface area of ​​the positive electrode material powder particles was measured using a Micromeritics ASAP2460 fully automatic specific surface analyzer.

[0092] (2) Compaction density test The compaction density of the positive electrode material powder was measured using an FTYS-50KN powder compaction density instrument.

[0093] (3) Preparation of button batteries The lithium iron manganese phosphate positive electrode material, the conductive agent acetylene black and the adhesive polyvinylidene fluoride were uniformly mixed in N-methylpyrrolidone at a mass ratio of 92:4:4 to make a slurry, which was then coated on an aluminum foil and dried in a vacuum drying oven. It was then pressed into a positive electrode sheet using a tablet press. The negative electrode sheet was a metal lithium sheet, the electrolyte was 1 mol / L lithium hexafluorophosphate-ethylene carbonate: dimethyl carbonate (LiPF6-EC:DMC, volume ratio of 1:1), a polypropylene porous membrane was used as a separator, and the battery was assembled in an argon glove box.

[0094] (4) Electrochemical performance test The electrochemical performance of the assembled button cell was tested in the charge and discharge voltage range of 2.5-4.5 V. The test results are shown in Table 1.

[0095] Table 1

[0096] From the attached figure, it can be concluded that: Figure 2 The SEM image shows that the primary particle size of the lithium manganese iron phosphate material prepared by the present invention is 300-500nm, and the particle size is uniform; Figure 3 The XRD diagram shows that the lithium manganese iron phosphate solid solution material prepared by the present invention is a pure phase, and there is no two-phase separation or impurity phase.

[0097] From Table 1 we can see that: It can be seen from Examples 1-14 that the present invention first constructs a lithium manganese phosphate precursor (LMP@LFP) coated with a lithium iron phosphate precursor slurry, and then prepares the lithium manganese iron phosphate positive electrode material in situ by a first-stage sintering, cooling and second-stage sintering process. The material has a high specific capacity, long cycle performance and high compaction density.

[0098] By comparing Example 1 with Examples 9-10, it can be seen that in the preparation process of the lithium manganese iron phosphate positive electrode material of the present invention, the particle size of the solid in the mixed solution after sand grinding in step S2 will affect its performance. When the solid particle size is controlled within an appropriate range, the electrical properties of the obtained positive electrode material are better; when the solid particle size is too large or too small, the diffusion rate of lithium ions in the material will decrease, the surface reaction active sites will decrease, and the specific capacity of the lithium battery prepared from the positive electrode material will be reduced.

[0099] By comparing Example 1 with Examples 11-12, it can be seen that in the preparation process of the lithium manganese iron phosphate positive electrode material of the present invention, the molar ratio of manganese and iron elements will affect its performance. If the manganese iron is relatively low, the manganese dissolution problem of the material is small, and the specific capacity of the lithium battery prepared therefrom increases, the powder compaction density of the material increases, and the cycle performance improves; if the manganese iron is relatively high, the manganese dissolution problem of the material is aggravated, resulting in a decrease in the specific capacity of the lithium battery prepared therefrom, a decrease in the powder compaction density of the material, and a deterioration in the cycle performance.

[0100] By comparing Example 1 with Examples 13-14, it can be seen that in the preparation process of the lithium manganese iron phosphate positive electrode material of the present invention, the temperature of the second-stage sintering will affect its performance. If the sintering temperature is low, the internal defect elimination effect of the material is good, and the positive electrode material has a higher specific capacity and better cycle performance; if the sintering temperature is too high, the manganese content on the particle surface increases, and the internal defect elimination effect is poor, the positive electrode material has a lower specific capacity and a worse cycle performance. By comparing Example 4 with Comparative Example 1, it can be seen that in step S1, the precursor of lithium manganese iron phosphate is formed in Comparative Example 1 when mixed, and then lithium manganese iron phosphate is obtained by sintering, and the lithium manganese phosphate is not coated with lithium iron phosphate precursor slurry and then solid-dissolved in situ. From the data results, whether it is specific capacity or compaction density, Comparative Example 1 is worse than Example 4, and the long cycle performance is particularly obvious. The reason is that the LMP@LFP precursor structure and preparation process constructed in Example 4 can inhibit Mn 3+ The dissolution during the cycle results in better cycle performance of the positive electrode material. However, in the method of directly mixing and sintering the lithium source, iron source, manganese source and phosphorus source to prepare lithium manganese iron phosphate in comparative example 1, the size of the material particles is small and the specific surface area is large during the synthesis process, and the conductivity and capacity of the material are also poor.

[0101] By comparing Example 5 with Comparative Example 2, it can be seen that Comparative Example 2 does not perform the second stage sintering in step S2, and lacks a low-temperature tempering process. From the data results, the specific capacity and cycle performance of the positive electrode material of Comparative Example 2 are significantly worse than those of Example 5. The reason is that the two-stage sintering process set in step S2 of Example 5 has significantly different functions. The first stage sintering is a high-temperature insulation stage, which uses the fast diffusion rate of manganese atoms at high temperature to promote the in-situ solid solution of manganese and iron, and then prepare lithium manganese iron phosphate. The role of the second stage sintering is to eliminate the structural defects and residual stress generated in the material during the high-temperature solid solution process at low temperature, thereby improving the diffusion of lithium ions, ensuring the perfect performance of the capacity of the positive electrode material and reducing the attenuation of long cycles.

[0102] By comparing Example 5 with Comparative Example 3, it can be seen that the iron source used in the second mixing process of step S2 in Comparative Example 3 is insoluble iron phosphate, and Example 5 uses soluble iron source ferrous sulfate. From the data results, the specific capacity, cycle performance and compaction density of the positive electrode material of Comparative Example 3 are significantly worse than those of Example 5. The reason is that the coating effect of insoluble iron salt on the surface of lithium manganese phosphate is not good, and the effect of in-situ solid solution is not as good as that of soluble iron salt, so the electrochemical performance is not as good as that of Example 5; as for the low compaction density, it is because the coating effect of insoluble iron salt is poor, resulting in too high a proportion of lithium manganese phosphate, which reduces the overall compaction density of the material.

[0103] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: The lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source are subjected to a second mixing and a second drying to obtain a precursor; the precursor is subjected to a first-stage sintering, a cooling, and a second-stage sintering to obtain a lithium manganese iron phosphate positive electrode material.

2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The atmosphere of the first-stage sintering, cooling and second-stage sintering process is nitrogen or argon; And / or, the sintering temperature of the first stage sintering is 700-850°C, and the sintering time is 6-12h; And / or, the temperature is lowered to 200-350° C. after a sintering step; And / or, the sintering temperature of the second stage sintering is 600-750° C., and the sintering time is 4-8 hours.

3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The second mixing includes adding the lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source into water to prepare a second mixed solution, wherein the total mass fraction of the lithium manganese phosphate material, the iron source, the second phosphorus source, the second lithium source, the dopant M and the carbon source in the second mixed solution is 20%-60%; performing a second sand milling on the second mixed solution to control the particle size D50 of the solid in the second mixed solution to be 0.35~0.60 μm.

4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The iron source is a soluble iron salt or iron hydroxide; and / or, the dopant M comprises at least one of compounds of magnesium, titanium, vanadium, niobium, chromium and cerium; And / or, the carbon source includes at least one of glucose, sucrose, polyvinyl alcohol, polyacrylamide, polyvinyl pyrrolidone, chitosan, melamine, fructose, cyclodextrin and polyethylene glycol.

5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the lithium element in the second lithium source, the iron element in the iron source and the phosphorus element in the second phosphorus source is (1-1.05):1:(1-1.03); And / or, the molar ratio of the metal element in the dopant M to the iron element in the iron source is (0.005-0.05):1; And / or, the molar ratio of the iron element in the iron source to the manganese element in the lithium manganese phosphate material is (1-5): (5-9); And / or, the mass of the carbon source is 10%-20% of the theoretical output mass of carbon-free lithium iron manganese phosphate.

6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The preparation method of the lithium manganese phosphate material comprises: first mixing a manganese source, a first phosphorus source, a first lithium source and a dopant N, and freeze-drying to obtain a dried material; and sintering the dried material to obtain the lithium manganese phosphate material.

7. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: The manganese source includes at least one of manganese oxide, manganese hydroxide, soluble manganese salt, manganese carbonate and manganese phosphate; and / or, the first phosphorus source or the second phosphorus source comprises at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphorus pentoxide; and / or, the first lithium source or the second lithium source comprises at least one of lithium carbonate, lithium hydroxide, lithium phosphate, lithium oxalate, lithium acetate and lithium nitrate; And / or, the dopant N includes at least one of compounds of magnesium, titanium, nickel, aluminum, vanadium, niobium, cobalt, chromium and cerium.

8. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 6, characterized in that: The first mixing includes adding the manganese source, the first phosphorus source, the first lithium source and the dopant N into water to prepare a first mixed solution, wherein the total mass fraction of the manganese source, the first phosphorus source, the first lithium source and the dopant N in the first mixed solution is 20%-60%; performing a first sand milling on the first mixed solution to control the particle size D50 of the solid in the first mixed solution to be 0.2-0.4 µm; and / or, the molar ratio of the manganese element in the manganese source, the lithium element in the first lithium source, and the phosphorus element in the first phosphorus source is 1:(1-1.05):(1-1.03); And / or, the molar ratio of the metal element in the dopant N to the manganese element in the manganese source is (0.005-0.05):

1.

9. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 6, characterized in that: The sintering atmosphere includes at least one of nitrogen, argon, 95% nitrogen / 5% hydrogen and 95% argon / 5% hydrogen; And / or, the sintering temperature is 500-650° C. and the sintering time is 2-8 hours.

10. Use of the lithium iron manganese phosphate positive electrode material prepared by the method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 9 in a lithium ion battery.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate and preparation method and application therefor

    CN105226273A

  • Lithium ferric manganese phosphate positive electrode material with iron and manganese elements in full-concentration gradient distribution and preparation method of lithium ferric manganese phosphate positive electrode material

    CN114725340A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN115775878A

  • Lithium manganese iron phosphate positive electrode material, preparation method and application thereof, and lithium ion battery

    CN116332147A

  • Doping preparation method of lithium iron manganese phosphate composite positive electrode material

    CN117303337A